Pakui Sayang Park: A History of Public Space Development in Makassar City - Fadillah Usman, Sahra; Ahmadin; Asmunandar (Jurnal Ekonomi dan Riset Pembangunan, 2024)
This study aims to determine the background of the construction of Pakui Sayang Park, the function and role of Pakui Sayang Park and the social impact of the presence of this park as a Public Space in Makassar City. The temporal of this study starts from 2016, which is the year when the park was built, until 2023, when the most recent data on the existence of this public space can be obtained. This research uses historical research methods, with stages: heuristic, source criticism, interpretation, and historiography. The results of the study show that the background of the construction of Pakui Sayang Park is the emergence of a series of ideas that were energized by the existence of an unkempt and very alarming vacant land in the General Revenue Office area on Jalan A.P. Pettarani. For this reason, the Makassar City government built Pakui Sayang Park to become one of the sports venues and become a Green Open Space. The utilization of Pakui Sayang Park as a public space includes the location of major events such as Ramadan bazaars and concerts, sports facilities, and a place to relax.